PERAN CUSTOMER SATISFACTION DALAM MEMEDIASIKAN PENGARUH SERVICE QUALITY TERHADAP CUSTOMER LOYALTY PADA BALAI BESAR KARANTINA PERTANIAN TANJUNG PRIOK - Mardi Riyanto (Jurnal Manajemen Dayasaing, 2022)
The main job of the Tanjung Priok Agricultural Quarantine Center is quarantine services to the community, so it is important to examine how customers perceive services and their implications for customer loyalty. This study aims to analyze the effect of service quality on customer loyalty, either directly or indirectly. This research approach is quantitative type of causality. The research population is Balai Besar Karantina Pertanian (BBKP) Tanjung Priok customers, both for export-import and domestic purposes. The data collection technique used a survey with a closed questionnaire research instrument using a Likert Scale 1-6. The data analysis technique uses Structural Equation Modeling (SEM), in this case Partial Least Square (PLS), and path analysis. The results showed that service quality had a positive and significant effect on customer loyalty on BBKP Tanjung Priok.. The results of this study mean that the higher the level of Service Quality, the more Customer Loyalty at BBKP Tanjung Priok. Customer satisfaction partial mediates the effect of service quality on customer loyalty.